2018
DOI: 10.1590/s1519-99402018000100002
|View full text |Cite
|
Sign up to set email alerts
|

Biomass components of Pennisetum purpureum cv. Roxo managed at different growth ages and seasons

Abstract: SUMMARY This study was carried out aiming to evaluate the biomass components of elephant grass cv. Roxo at seven growth ages, during rainy, transition and dry seasons. A completely randomized design was adopted with a split plot arrangement over time. The treatments consisted of seven growth ages (9, 18, 27, 36, 45, 54 and 63) and three seasons (rainy, transition and dry). The variables green forage biomass, dead forage biomass, green stem biomass and green leaf blade biomass showed positive linear responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
2
1
0
1
Order By: Relevance
“…The different climatological conditions in the rainy and dry seasons were decisive in the modification of this agronomic characteristic. The LAI value of CT-115 and Maralfalfa doubled in the rainy season with respect to the dry season (Table 1 and 2), which was also reported by Maranhão et al [32], upon evaluation of a species of the Cenchrus genus in eastern Brazil along three climatologically defined periods (rainy, transitional, and dry) and different cutting ages. In their research, they found that LAI was two times greater in the rainy season, in comparison with the dry season; additionally, according to their results and analysis, they determine that there is a positive correlation with age.…”
Section: Discussionsupporting
confidence: 79%
“…The different climatological conditions in the rainy and dry seasons were decisive in the modification of this agronomic characteristic. The LAI value of CT-115 and Maralfalfa doubled in the rainy season with respect to the dry season (Table 1 and 2), which was also reported by Maranhão et al [32], upon evaluation of a species of the Cenchrus genus in eastern Brazil along three climatologically defined periods (rainy, transitional, and dry) and different cutting ages. In their research, they found that LAI was two times greater in the rainy season, in comparison with the dry season; additionally, according to their results and analysis, they determine that there is a positive correlation with age.…”
Section: Discussionsupporting
confidence: 79%
“…Roxo showing positive linear behavior, it was noticed that the accumulation of those nutrients was greatest between the ages 27 and 36 DAC in the rainy season and between the ages 36 and 45 DAC for the transition season. The response in the present study is justified by the maximum population density of tillers being observed at 31 and 39 DAC in the rainy and transition seasons, respectively, as observed by Maranhão et al (2018). As for the dry season, the accumulation of nutrients was enhanced between the ages of 18 and 27 DAC.…”
supporting
confidence: 71%
“…In tropical regions, rain is the main factor that limits the growth and accumulation of forage mass, and it has been verified that the seasonality of rainfall influences the increase in biomass of Pennisetum purpureum cv. Roxo (16). The seasonality of Brachiaria brizantha cv.…”
Section: Introductionmentioning
confidence: 99%